Uruguay : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
The paper examines the extent to which the recent evolution of the consolidated public sector balance in Uruguay reflects the business cycle. Fiscal policies have generally been cautious, even though some structural reforms, the electoral cycle, and recessions in recent years increased the deficit. Bank soundness indicators differ substantially between private and public banks in Uruguay. The private banking system appears sound. Public banks did not fare as well during the recession, and their soundness needs to be addressed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet